Role of Design Technology in Optimization of Transportation: A Study on Tripadam Logistics Private Limited, Chennai (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The rapid transformation of the Indian logistics sector, driven by the proliferation of e-commerce, cross-border trade, and just-in-time supply chain models, has placed transportation at the centre of organizational efficiency. This study investigates the role of design technology in optimizing transportation operations at Tripadam Logistics Private Limited, a Chennai-based integrated logistics service provider incorporated in 2009. The research adopts a descriptive and analytical research design, drawing on primary data collected through structured questionnaires administered to 50 employees and stakeholders. Statistical tools including percentage analysis, one-way ANOVA, chi-square tests, correlation analysis, and one-sample t-tests were employed to evaluate relationships between technology adoption and operational outcomes. Findings reveal that technologies such as GPS tracking, AI-powered route optimization, IoT sensors, cloud-based logistics platforms, and automated dispatch systems have significantly improved route efficiency, vehicle capacity utilization, delivery accuracy, and customer satisfaction. The study contributes actionable insights for mid-sized Indian logistics firms seeking to leverage design-tech solutions to remain competitive in an evolving market environment.